2009
DOI: 10.2353/ajpath.2009.080240
|View full text |Cite
|
Sign up to set email alerts
|

The Long Pentraxin PTX3 Is Crucial for Tissue Inflammation after Intestinal Ischemia and Reperfusion in Mice

Abstract: The pentraxin superfamily is a group of evolutionarily conserved proteins that play important roles in the immune system. The long pentraxin PTX3 protein was originally described as able to be induced by pro-inflammatory stimuli in a variety of cell types. In this study, we evaluated the phenotype of Ptx3 ؊/؊ mice subjected to ischemia followed by reperfusion of the superior mesenteric artery. In reperfused wildtype mice, there was significant local and remote injury as demonstrated by increases in vascular pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 43 publications
5
81
1
Order By: Relevance
“…The area under the receiveroperating characteristic curve (AUC) values and 95% confidence intervals are given for the 3 analyzed variables. 33,34 In agreement, PTX3-overexpressing mice had greater tissue damage and mortality after reperfusion of the ischemic vascular bed. 35 Our finding that PTX3 is harmful for the mesenteric district is fully in agreement with previous reports suggesting that therapeutic blockade of the action of PTX3 may be useful for injuries associated with severe ischemia and reperfusion syndromes in the this area.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The area under the receiveroperating characteristic curve (AUC) values and 95% confidence intervals are given for the 3 analyzed variables. 33,34 In agreement, PTX3-overexpressing mice had greater tissue damage and mortality after reperfusion of the ischemic vascular bed. 35 Our finding that PTX3 is harmful for the mesenteric district is fully in agreement with previous reports suggesting that therapeutic blockade of the action of PTX3 may be useful for injuries associated with severe ischemia and reperfusion syndromes in the this area.…”
Section: Discussionsupporting
confidence: 60%
“…A careful analysis of data revealed that overexpression of the protein is induced by different stimuli. 33,35 So far, there are no available data on blood pressure in this experimental condition, and future studies will need to pursue this goal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the participation of the long pentraxin 3 (PTX3) in TxA-induced enteritis based on our previous findings pointing out the pivotal role of this protein in injury following intestinal ischemia and reperfusion (49,50). TxA promoted an increase in Ptx3 gene expression in ileal tissue of mice with TxA-induced enteritis compared to that of PBS-injected mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB activation was investigated by Western blotting analysis of nuclear cell extracts obtained from homogenized soleus muscle, as described previously (27). Briefly, tissue was homogenized in 1 mL ice-cold hypotonic lysis buffer (10 mM Tris, pH 7.4, 10 mM NaCl, 3 mM MgCl 2 , 0.002% NaN 3 , 1 mM PMSF, 0.1 mM EGTA, 10 µM aprotinin, 20 µM leupeptin, 0.5 mM DTT, 25 mM NaF) and chilled on ice for 15 min and 5% NP-40 was then added for a further 5 min.…”
Section: Nf-κb Activation In Soleus Musclementioning
confidence: 99%